Karakteristik Permen Gummy Probiotik Dengan Isolat Lokal Lacticaseibacillus paracasei RB210 Selama Penyimpanan Pada Suhu Dingin - Adina Chara Andisa; Ni Nyoman Puspawati; Ni Made Indri Hapsari Arihantana (Itepa : Jurnal Ilmu dan Teknologi Pangan, 2026)
Candy is a fun food enjoyed by of all ages, with gummy candy being one of the most popular due to its chewy texture. Various innovations have been made to enhance its functional value by adding nutritious ingredients such as tamarind turmeric, ginger, citrus extract, or probiotic microorganisms like Lacticaseibacillus paracasei RB210. One factor that affecting the quality of probiotic gummy candy is storage duration, which tends to reduce the number of viable probiotic bacteria. This study aims to evaluate the effect of cold storage duration on the characteristics and viability of Lacticaseibacillus paracasei RB210 in probiotic gummy candy and to evaluate its characteristics and viability over a four-week storage period. A Completely Randomized Design (CRD) was used with five treatment durations (0, 1, 2, 3, and 4 weeks), each replicated three times for a total of 15 experimental units. Data were analyzed using Analysis of Variance (ANOVA), and if significant effects were found, Duncan’s multiple range test was applied. Observed parameters included moisture content, water activity (aw), reducing sugar, chewiness, total lactic acid bacteria (LAB), total yeast and mold, and sensory evaluation. The results showed that cold storage duration significantly affected moisture content, reducing sugar, chewiness, total LAB, and sensory attributes of texture and overall acceptance, but had no significant effect on water activity, yeast and mold count, or the sensory attributes of aroma, color, and taste. Storage for up to 4 weeks was still able to maintain the characteristics and viability of Lacticaseibacillus paracasei RB210 in probiotic gummy candy, with characteristics including moisture 38.57%, aw 0.92, reducing sugar 7.37%, chewiness 66.66 N, total LAB 8.55 log CFU/g, total yeast and mold 3.43 log CFU/g, favorable acceptance for color and taste, slightly favorable for aroma and flavor, chewy texture, and favorable acceptance for overall acceptability.